2002
DOI: 10.1097/00008571-200212000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Identification and functional characterization of new potentially defective alleles of human CYP2C19

Abstract: CYP2C19 is a clinically important enzyme responsible for the metabolism of a number of therapeutic drugs, such as mephenytoin, omeprazole, diazepam, proguanil, propranolol and certain antidepressants. Genetic polymorphisms in this enzyme result in poor metabolizers of these drugs. There are racial differences in the incidence of the poor metabolizer trait, which represents 13-23% of Asians but only 3-5% of Caucasians. In this study, single nucleotide polymorphisms (SNPs) in CYP2C19 were identified by direct se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(100 citation statements)
references
References 25 publications
12
87
1
Order By: Relevance
“…P450 2C19*1A differs from P450 2C19*1B due to a nonsynonymous single nucleotide polymorphism (refSNP rs3758581) that changes codon 331 for valine in the CYP2C19*1B gene to a codon for isoleucine, which is present in NCBI reference sequence for the CYP2C19*1A gene (NG_008384.1). The corresponding proteins do not appear to differ in their catalytic properties (28,29). A three-fragment ligation reaction was used to insert two fragments, generated by SacI/SphI and SphI/ PvuII digestion of pCW2C19*1B plasmid (27), into the pCW2C5LVdH expression vector (30) digested with SacI and PvuII.…”
Section: Methodsmentioning
confidence: 99%
“…P450 2C19*1A differs from P450 2C19*1B due to a nonsynonymous single nucleotide polymorphism (refSNP rs3758581) that changes codon 331 for valine in the CYP2C19*1B gene to a codon for isoleucine, which is present in NCBI reference sequence for the CYP2C19*1A gene (NG_008384.1). The corresponding proteins do not appear to differ in their catalytic properties (28,29). A three-fragment ligation reaction was used to insert two fragments, generated by SacI/SphI and SphI/ PvuII digestion of pCW2C19*1B plasmid (27), into the pCW2C5LVdH expression vector (30) digested with SacI and PvuII.…”
Section: Methodsmentioning
confidence: 99%
“…The allele was first described in Black Africans by Blaisdell et al [20], where the defining SNV, 55A>C (rs17882687), was found to be in linkage disequilibrium with 80161A>G (rs3758581).…”
Section: Cyp2c19 Comparison Between Predicted and Measured Phenotypementioning
confidence: 99%
“…To achieve this, additional alleles such as the decreased function CYP2C19*9 and *15 alleles were accounted for in this study. The former allele was of particular relevance, as it is known to be African-specific [20,21] and indeed contributed to the improved stratification of CYP2C19 phenotypes.…”
Section: Cyp2c19 Comparison Between Predicted and Measured Phenotypementioning
confidence: 99%
See 2 more Smart Citations